1963
DOI: 10.1111/imj.1963.12.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis in Autoimmune Hæmolytic Anæmia

Abstract: SUMMARY Factors reported to influence the prognosis for patients with autoimmune hæmolytic anæmia are reviewed and compared with experience at the Postgraduate Medical School, London. In the idiopathic warm‐antibody type of hæmolytic anæmia, prognosis depends on the amount of antibody formed and its quality. Of 50 patients in the London series, 23 died, mostly within two years of the onset of the disease, whilst 10 underwent clinical and hæmatological cure. The idiopathic cold‐antibody type of disease is in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1963
1963
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The occurrence of more than one case of AIHA in the same family is, however, most unusual, but it has happened. The author (Dacie, 1969) reported that he had encountered only one example – a sister and brother – out of more than 100 cases of AIHA seen up to that time. Writing in 1992, he was, however, able to list 20 published descriptions of the occurrence of AIHA in more than one family member, included in the relationships were four pairs of twins.…”
Section: Aiha: the Role Of Genetic Factorsmentioning
confidence: 99%
“…The occurrence of more than one case of AIHA in the same family is, however, most unusual, but it has happened. The author (Dacie, 1969) reported that he had encountered only one example – a sister and brother – out of more than 100 cases of AIHA seen up to that time. Writing in 1992, he was, however, able to list 20 published descriptions of the occurrence of AIHA in more than one family member, included in the relationships were four pairs of twins.…”
Section: Aiha: the Role Of Genetic Factorsmentioning
confidence: 99%
“…No specific treatment of the C.A.S. is available (5). Steroids, cytotoxic agents (e. g. urethane, nitrogen mustard) and radiation therapy (thorotrast, radioactive gold, X-ray) have been tried with the aim of reducing the production of cold agglutinins, b u t without success.…”
mentioning
confidence: 99%